Okoljsko poročilo z dodatkom za širitev igrišča za golf v Lipici - Smrekar, Aleš (ZRC SAZU, Založba ZRC, 2009)
The plan of spatial arrangement, which was given to us by the real estate developer to asses (environmental report and the estimation of the susceptibility of impacts on protected areas), deals with 80 hectars of the north-western part of Lipica Stud Farm, which covers the area of the existing golf course as well as the area of its foreseen expansion. We tried to establish, describe and evaluate all the important aspects of plan realization, taking into consideration all of the environmental goals and area characteristics based on the different segments of the environment. A major impact would be seen only in the potentially special protected area of Kras, more precisely on the group of beetles, among which we stress "Morimus funereus" as the qualification bird species of Natura 2000. We suggested the exclusion of 17 hectars of the area from further operations and the establishment of the new distribution of some individual golf-fields. The improved suggestion incorporates the exclusion of a stripe of the western part of the area in question, where there is a habitat of Morimus funereus. This change would also mean the preservation of fossile sites and of maple forests.